Impacto da restrição energética para perda de massa corporal com diferentes proporções de carboidratos na dieta de praticantes de Brazilian Jiu-Jitsu - Costa, Dayanne da (2016)
INTRODUCTION: The combat sports tournaments are divided by rigid strips weight, aiming to balance disputes, minimizing the differences among the competitors. One of the methods for rapid body mass loss is calorie restriction with consequent reduction of carbohydrate, which despite its efficacy has been an area of controversy. OBJECTIVE: To analyze the effect of two nutritional strategies for gradual loss of body mass with different proportions of carbohydrates among Jiu Jitsu practitioners. METHODS: Study of clinical type, with 18 practitioners of Brazilian Jiu-Jitsu for two months with dietary intervention 28 days, the sample was divided into two groups (reduction of carbohydrate - R-CHO and appropriate carbohydrate - A-CHO). They assessed the nutritional status, body composition, psychological state, hormonal parameters and physical tests, and dietary monitoring. The statistical analysis used was a two-way ANOVA, with the significance level of p = 0.05. RESULTS: Most practitioners (88.9%) in both groups were able to obtain the loss of body mass with fitness category (> 3%), and the consequent decrease in BMI and body fat percentage, without using dehydration. The power of the lower limbs was significantly greater after nutritional intervention for R-CHO group (Δ = 0,030). In relation to hormone data was increased T4 to R-CHO (Δ = 0,553) group and decreased Free T4 for group ACHO (Δ = -0,081). In relation to diet adherence monitoring, both groups decreased daily calories, and only the R-CHO group had a significant decrease in carbohydrate without decreasing frequency of training and without a change in mood. CONCLUSION: Participants undergo a diet with reduced carbohydrate and regular training, got lost effective body mass without negative change in physical performance and minimizing hormonal changes.